The Effect of Motivation and Discipline on Employee Performance at Depok Mayor's Office - Maduningtias, Lucia (PINISI Discretion Review, 2018)
This human resource factor is an element that must be considered by each agency. The purpose of this study was to determine the effect of motivation and discipline on employee performance at the Depok Mayor's Office. The method used in this research is descriptive with an associative approach, the sampling technique used is proportional random sampling using the census or saturated sampling method with a sample of 50 respondents. The analysis tool uses instrument testing, classical assumption testing, regression testing, correlation coefficient testing and coefficient of determination and hypothesis testing. The results of the study concluded that there was a positive and significant effect both partially and simultaneously between motivation and discipline on employee performance at the Depok Mayor's Office. The level of influence or strength of the relationship simultaneously is 0.690 or strong with the contribution of influence of 0.476 or 47.6% while the remaining 52.4% is influenced by other factors. Hypothesis testing is obtained Fcount> Ftable (21,230> 2,800) thus H0 is rejected and H3 is accepted meaning that there is a positive and significant effect simultaneously between motivation and discipline on employee performance at Depok Mayor's Office